Complexation with pre-formed “empty” V-type starch for encapsulation of aroma compounds - Jingyi Zhou; Lingyan Kong (Food Science and Human Wellness)
Aroma compounds are low-molecular-weight organic volatile molecules and are broadly utilized in the food industry. However, due to their high volatility and evaporative losses during processing and storage, the stabilization of these volatile ingredients using encapsulation is a commonly investigated practice. Complexation of aroma compounds using starch inclusion complex could be a potential approach due to the hydrophobicity of the left-handed single helical structure. In the present study, we used starch of three different V-type structures, namely V6h, V7, and V8, to encapsulate six different aroma compounds, including 1-decanol (DN), cis-3-hexen-1-ol (HN), 4-allylanisole (AN), γ-decalactone (DA), trans-cinnamaldehyde (CA), and citral (CT). The formed inclusion complexes samples were characterized using complementary techniques, including X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The results showed that upon complexation with aroma compounds, all V-subtypes retained their original crystalline structures. However, different trends of crystallinity were observed for each type of the prepared inclusion complexes. Additionally, among three V-type starches, V6h-type starch formed inclusion complexes with aroma compounds most efficiently and promoted the formation of Form II complex. This study suggested that the structure of aroma compounds and the type of V starch could both affect the complexation properties.